Basic Principles and Calculations in Chemical Engineering - Himmelblau, David Mautner ((Prentice-Hall International Series in the Physical and Chemical Engineering Sciences))
Contenido: 1) Introducción; 2) Balances de materia; 3) Gases, vapores, líquidos y sólidos; 4) Balances de energía; 5) Material suplementario del CD acompañante.